2001
DOI: 10.1038/35086595
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination-dependent mechanisms regulate synaptic growth and function

Abstract: The covalent attachment of ubiquitin to cellular proteins is a powerful mechanism for controlling protein activity and localization. Ubiquitination is a reversible modification promoted by ubiquitin ligases and antagonized by deubiquitinating proteases. Ubiquitin-dependent mechanisms regulate many important processes including cell-cycle progression, apoptosis and transcriptional regulation. Here we show that ubiquitin-dependent mechanisms regulate synaptic development at the Drosophila neuromuscular junction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
307
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(322 citation statements)
references
References 23 publications
(21 reference statements)
14
307
1
Order By: Relevance
“…Overexpression of faf in the developing Drosophila nervous system causes synaptic overgrowth and perturbs synaptic transmission. A similar phenotype is observed when a yeast DUB is expressed in the fruit fly CNS (DiAntonio et al 2001).…”
Section: Dubssupporting
confidence: 67%
“…Overexpression of faf in the developing Drosophila nervous system causes synaptic overgrowth and perturbs synaptic transmission. A similar phenotype is observed when a yeast DUB is expressed in the fruit fly CNS (DiAntonio et al 2001).…”
Section: Dubssupporting
confidence: 67%
“…Ubiquitination has previously been implicated in the cell survival response under conditions of stress, morphogenesis, organogenesis, and exocytosis. It has also been shown to be important in hippocampal long-term potentiation in mice [19] and in the growth of presynaptic nerve terminals in Drosophila [20]. This is interesting because the present studies also showed upregulation of the annexin V protein, which has been shown to have neurotrophic effects on cultured neurons [11].…”
Section: Discussionsupporting
confidence: 68%
“…The following flies were used: fmi E59 , UAS-Fmi, UAS-ÎEx (28), Df(2R)stan 2 , fmi 72 (34), elav-Gal4 (DiAntonio et al, 2001), fmi 1071 and fmi 1127 . fmi mutant alleles and the deficiency line were balanced with CyO KrGFP allowing easy selection of GFP-negative fmi mutant larvae (Gao et al, 2000).…”
Section: Fly Strains and Geneticsmentioning
confidence: 99%
“…Other molecules are more directly involved in synaptogenesis, synaptic growth, or maintenance. These molecules include bone morphogenetic protein (Alberle et al, 2002;Marques et al, 2002;Rawson et al, 2003;McCabe et al, 2003;Keshishian and Kim, 2004), ubiquitin (Oh et al, 1994;DiAntonio et al, 2001;Murphey and Godenschwege, 2002;DiAntonio and Hicke, 2004), cell adhesion molecules (Washbourne et al, 2004), and Wingless signaling components (Packard et al, 2003;Charron and Tessier-Lavigne, 2005).…”
Section: Introductionmentioning
confidence: 99%